2016
DOI: 10.1080/17425255.2016.1184648
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of pain in painful diabetic neuropathy

Abstract: Introduction: Painful diabetic neuropathy (PDN) is a disabling pain condition. Its pathomechanism remains unknown, but a sensitization and neuronal hyperexcitabilty have been suggested. Only symptomatic pharmacological pain-alleviation treatment is currently available. Areas covered:The origin of PDN is enigmatic, and the evidence-based therapeutic guidelines therefore consist only of antidepressants and antiepileptics as first-line recommended drugs. This article relates to a MEDLINE/PubMed systematic search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 122 publications
0
6
0
Order By: Relevance
“…Due to its high frequency, PDP was the prototype disorder for the development of anti-NP therapeutic strategies. The first-line drugs in PDP as recommended by different international therapeutic guidelines are the following: duloxetine, gabapentin, pregabalin, TCAs (amitriptyline), and venlafaxine ER (extended release) [12, 39, 40]. Cochrane meta-analyses concluded that gabapentin, pregabalin, and duloxetine are effective for pain relief in PDP [31, 41, 42].…”
Section: Chronic Peripheral Npmentioning
confidence: 99%
“…Due to its high frequency, PDP was the prototype disorder for the development of anti-NP therapeutic strategies. The first-line drugs in PDP as recommended by different international therapeutic guidelines are the following: duloxetine, gabapentin, pregabalin, TCAs (amitriptyline), and venlafaxine ER (extended release) [12, 39, 40]. Cochrane meta-analyses concluded that gabapentin, pregabalin, and duloxetine are effective for pain relief in PDP [31, 41, 42].…”
Section: Chronic Peripheral Npmentioning
confidence: 99%
“…The development of DNP is dependent on two critical pathogenic factors: the metabolic factor and the vascular factor. The primary metabolic mechanisms include hyperglycemia-activated polyhydric alcohol pathway, accumulation of sorbitol and fructose, inositol reduction, non-enzymatic protein glycosylation, and oxidative stress 3 , 4 . The vascular mechanism is the consequence of diabetes-induced systemic microvascular damage; it leads to energy and nutrient deficiency, inducing a hypoxic and ischemic injury of neural cells.…”
Section: Introductionmentioning
confidence: 99%
“…Pregabalin is a structural analogue of the inhibitory neurotransmitter gamma‐aminobutyric acid (GABA) and binds to the α 2 δ auxiliary subunit of voltage‐gated calcium channels in the central nervous system. In clinical trials, pregabalin has been shown to have analgesic effects in diabetic neuropathy, post‐herpetic neuralgia and spinal cord injury (Offord & Isom, ; Patel & Dickenson, ; Tatji et al, ). In controlled clinical trials involving peripheral neuropathic pain, 35% of pregabalin‐treated patients had an improvement in their pain scores (Satoh et al, ).…”
Section: Discussionmentioning
confidence: 99%